2016
DOI: 10.1002/lsm.22442
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyclic loading on the adhesive effectiveness of resin‐zirconia interface after femtosecond laser irradiation and conventional surface treatments

Abstract: Use of femtosecond laser irradiation could be an alternative to conventional surface treatments to achieve suitable adhesion zirconia and resin cements. Femtosecond laser irradiation at step 40 is preferable because it is more efficient and faster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…Six types of lasers were identified in the 52 articles analyzed in this review. A total of 14 studies included CO 2 laser [ 21 , 24 , 30 , 32 , 37 46 ]; six studies used Er,Cr:YSGG laser [ 22 , 30 , 47 50 ]; 23 articles included Er:YAG laser groups [ 9 , 10 , 31 , 32 , 37 , 44 , 51 67 ]; Femtosecond laser was used in six articles [ 25 , 26 , 53 , 55 , 68 , 69 ]; Nd:YAG in 18 of the studies [ 11 , 24 , 39 , 48 , 52 , 53 , 55 , 56 , 63 , 65 , 66 , 70 76 ]; and Yb:YAG laser was used in only one study [ 29 ]. The lasers were used with different power outputs, ranging from 400mW to 10W, femtosecond lasers using the lowest power, in contrast with Er:YAG and CO 2, which were set at the highest power outputs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six types of lasers were identified in the 52 articles analyzed in this review. A total of 14 studies included CO 2 laser [ 21 , 24 , 30 , 32 , 37 46 ]; six studies used Er,Cr:YSGG laser [ 22 , 30 , 47 50 ]; 23 articles included Er:YAG laser groups [ 9 , 10 , 31 , 32 , 37 , 44 , 51 67 ]; Femtosecond laser was used in six articles [ 25 , 26 , 53 , 55 , 68 , 69 ]; Nd:YAG in 18 of the studies [ 11 , 24 , 39 , 48 , 52 , 53 , 55 , 56 , 63 , 65 , 66 , 70 76 ]; and Yb:YAG laser was used in only one study [ 29 ]. The lasers were used with different power outputs, ranging from 400mW to 10W, femtosecond lasers using the lowest power, in contrast with Er:YAG and CO 2, which were set at the highest power outputs.…”
Section: Resultsmentioning
confidence: 99%
“…After the bonding procedure, and prior to bond strength tests, most articles reported storing samples in distilled water for 24 hours at 37°. Many studies carried out thermocycling using different protocols, but only one performed cyclic loading [ 25 ]. All the studies performed bond strength tests by means of a shear load at a crosshead speed of 0.5 or 1mm / min, with the exception of five studies, which performed microtensile tests at 0.1 and 0.5 mm / min [ 29 , 52 , 63 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present assay, the laser was set at a power output of 200mW, the chosen ablation pattern consisted of parallel lines separated by 60 μm and the samples were irradiated for 12 minutes. Due to the heterogeneity in terms of laser settings found in the published studies about femtosecond laser irradiation of ceramic surfaces [ 12 14 ], a pilot study was conducted by the authors (pending publication), to determine the ideal parameters, in which different power outputs and patterns were tested and irradiation time was optimized. The pilot study found these settings to be more effective in terms of SBS of brackets bonded to zirconia compared with the rest of the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have already introduced laser patterning to improve zirconia adhesive performance. Encouraging results were obtained from adhesion of veneer ceramics or resin cements to femto lased zirconia surfaces 26,27) .…”
Section: Discussionmentioning
confidence: 99%